Critical Media Literacy: A Pedagogy for New Literacies and Urban Youth - Mohammed Choudhury; Jeff Share (2012)
Teachers will learn a theoretical framework and practice pedagogical strategies for making their teaching more engaging and critical. In the 21st century when children are surrounded by highly constructed media messages selling everything from political ideologies to personal identities, it is imperative that schools prepare students to think critically about the information that surrounds them and also learn to create and express their voice in this digital age. This workshop is based on the Critical Media Literacy teacher education course at the University of California, Los Angeles (UCLA) as well as UNESCO’s (2011) Media and Information Literacy Curriculum forTeachers.